Identifying Bacterial and Host Factors Involved in the Interaction of Mycobacterium bovis with the Bovine Innate Immune Cells - Blanco, Federico Carlos; Gravisaco, María José; Bigi, María Mercedes; García, Elizabeth Andrea; Marquez, Cecilia; McNeil, Mike; Jackson, Mary; Bigi, Fabiana (Frontiers in Immunology, 2021)
Bovine tuberculosis is an important animal and zoonotic disease caused by Mycobacterium bovis. The innate immune response is the first line of defence against pathogens and is also crucial for the development of an efficient adaptive immune response. In this study we used an in vitro co-culture model of antigen presenting cells (APC) and autologous lymphocytes derived from peripheral blood mononuclear cells to identify the cell populations and immune mediators that participate in the development of an efficient innate response capable of controlling the intracellular replication of M. bovis. After M. bovis infection, bovine immune cell cultures displayed upregulated levels of iNOS, IL-22 and IFN-γ and the induction of the innate immune response was dependent on the presence of APC. Among the analysed M. bovis isolates, only a live virulent M. bovis isolate induced an efficient innate immune response and this response was increased when the M. bovis culture supernatant was used to stimulate the cell co-cultures. Moreover, we demonstrated that an allelic variation of the early secreted protein ESAT-6 (ESAT6 T63A) expressed in the virulent strain is involved in this increased innate immune response. These results highlight the relevance of the compounds secreted by live M. bovis as well as the variability among the assessed M. bovis strains to induce an efficient innate immune response.